2023
DOI: 10.1002/ehf2.14311
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐494 regulates high glucose‐induced cardiomyocyte apoptosis and autophagy by PI3K/AKT/mTOR signalling pathway

Abstract: Aims Diabetic cardiomyopathy (DCM) is one of the major cardiovascular complications of diabetes. However, the mechanism of DCM is not fully understood. Studies have confirmed that certain microRNAs (miRNAs/miRs) are key regulators of DCM. The aim of this study was to investigate the role and mechanism of microRNA (miR)‐494 in cardiomyocyte apoptosis and autophagy induced by high glucose (HG). Methods and results By establishing a rat DCM model and an HG‐treated H9c2 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Accumulating studies have demonstrated miRNAs directly target PI3K or its downstream components, which critically contributes to extensive cell events, including autophagy. , A previous study revealed that miR-155 mediated autophagy via directly targeting PI3K-AKT-mTOR in Schwann cells . We hypothesized that PI3K was also targeted by miR-155 to regulate Pec 1-induced autophagy inhibition in MH-S cells.…”
Section: Resultsmentioning
confidence: 92%
“…Accumulating studies have demonstrated miRNAs directly target PI3K or its downstream components, which critically contributes to extensive cell events, including autophagy. , A previous study revealed that miR-155 mediated autophagy via directly targeting PI3K-AKT-mTOR in Schwann cells . We hypothesized that PI3K was also targeted by miR-155 to regulate Pec 1-induced autophagy inhibition in MH-S cells.…”
Section: Resultsmentioning
confidence: 92%
“…The PI3K-Akt signaling pathway can regulate various cellular processes, which are closely related to cell proliferation, growth, metastasis, and apoptosis [33] . The PI3K-Akt signaling pathway has been found to play a cardioprotective role in cardiomyocytes by inhibiting apoptosis [34,35] . PI3K, fully known as phosphatidylinositol 3-kinase, has three different types [36] , of which only class I can act as lipid phosphorylator upon upstream signaling stimulation [37] .…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K-Akt signaling pathway can regulate various cellular processes, which are closely related to cell proliferation, growth, metastasis, and apoptosis 33 . The PI3K-Akt signaling pathway has been found to play a cardioprotective role in cardiomyocytes by inhibiting apoptosis 34 , 35 . PI3K, fully known as phosphatidylinositol 3-kinase, has three different types 36 , of which only class I can act as lipid phosphorylator upon upstream signaling stimulation 37 .…”
Section: Discussionmentioning
confidence: 99%